Credibility of Child Witnesses in Sri Lanka - Kiruthisha, M. (Faculty of Arts, University of Jaffna & Surana and Surana International Attorneys, 2026)
Sri Lankan courts apply a careful, fact-sensitive approach when assessing the competence and credibility of child witnesses. However, despite statutory safeguards and evolving judicial guidance, significant uncertainty remains as to how effectively trial courts evaluate child witness testimony in practice, particularly where social, financial, and environmental factors influence the child’s statement. Recent Court of Appeal decisions have reiterated that trial judges must conduct a careful preliminary assessment of competency and demeanour and that the risk of tutoring must be actively considered. The Evidence (Special Provisions) Act (No. 32 of 1999), the Criminal Procedure Amendments, and the Assistance to and Protection of Victims of Crime and Witnesses Act (No. 10 of 2023) provide statutory tools for receiving unsworn child testimony, admitting audio-visual interviews, and protecting child victims and witnesses. International guidance (UNODC/ specialized childvictim protocols) recommends trauma-informed, child-friendly procedures as many of which Sri Lankan practice and reforms are starting to adopt. The Indian Supreme Court’s State of Madhya Pradesh v. Balveer Singh (24 Feb 2025) summarised modern principles for child witness evidence (competence test, no minimum age bar, admissibility without mandatory corroboration where testimony inspires confidence), and offers useful doctrinal points for courts in Sri Lanka to consider when balancing caution against over-rejection of child testimony. The author analyses the practical application in Sri Lanka concerning the statements of child witnesses, revealing the significant influence of the social and financial background of the witness on the testimony given. Such factors often affect the credibility, consistency, and reliability of child witness statements, thereby having a broader impact on cases that substantially rely on child testimony. This work further discusses practical suggestions and possible measures that could be implemented to enhance and strengthen the reliability and evidentiary value of statements made by child witnesses.
Keywords: Child witnesses; Credibility; Evidence; Admissibility